Phytoseiid mites on conifers - Hajdú, Zsuzsanna; Szabó, Árpád; Pénzes, Béla (Acta Agraria Debreceniensis, 2010)
The abundance and species diversity of phytoseiids were studied in the evergreen collection of the Corvinus University of Budapest at Soroksár from March to August 2010. 329 phytoseiid mite specimens were collected from 15 cultivars of coniferous trees belonging to the following 4 genera: Juniperus, Abies, Picea and Pinus. 6 phytoseiid mite species have been identified: Amblyseius andersoni (Koch, 1957), Amblyseius tenuis Westerboer 1963, Anthoseius bakeri (Garman, 1948), Anthoseius involutus Livshitz et Kuznetzov 1972, Typhlodromus baccetti Lombardinii 1960 and Typhlodromus cotoneastri Wainstein 1963. The dominant phytoseiid species were Amblyseius andersoni and Anthoseius involutus.Amblyseius tenuis and Typhlodromus baccettii are new to the Hungarian fauna. Typhlodromus baccettii was found on Juniperus scopulorum 'Silver Star' and 'Moonglow' while Amblyseius tenuis was collected from Picea glauca 'Alberta Globe'.